Health and quality of life problems in Dentistry students - Díaz Cárdenas, Shyrley; Arrieta Vergara, Katherine; Guette Oliveros, Agustin (Universidad y Salud, 2017)
Objective: To associate health and quality of life problems related to health (QLRH) in Dentistry students at a public university in Cartagena, Colombia. Materials and methods: A cross-sectional study in 202 female students and 125 men was conducted. An instrument to investigate sociodemographic variables, health problems (presence of diseases in the last month) and quality of life related to health (WHOQOL-BREF) was designed and applied. The analysis included frequencies, proportions, Poisson regression with robust variance to associate domains and total score of the WHOQOL-BREF with sociodemographic variables and health problems. Results: 35.4% of students are sick and 61.8% present gastrointestinal diseases; according to WHOQOL-BREF, 55.3% perceive a state of good health and very good quality of life related to health. Being an adolescent student impacts positively on quality of life related to health. However, in the multivariate analysis, the variables that showed a negative impact were: depression, genitourinary and muscle skeletal alterations, chickenpox and skin problems (X2: 80.4, p= 0.001). Conclusions: Depression, genitourinary and muscle skeletal alterations, in addition to varicella and skin problems negatively impact on QLRH in dentistry students. It is required that the schools of dentistry promote healthy life styles that have an impact on the students’ quality of life.